Chronic dosing of a simulated pond ecosystem in indoor aquatic mesocosms: fate and transport of CeO2 nanoparticles. Issue 6 (25th September 2015) - Tella, M.; Auffan, M.; Brousset, L.; Morel, E.; Proux, O.; Chanéac, C.; Angeletti, B.; Pailles, C.; Artells, E.; Santaella, C.; Rose, J.; Thiéry, A.; et al.
Abstract : Indoor aquatic mesocosms were designed to mimic pond ecosystems contaminated by a continuous point-source discharge of cerium oxide nanoparticles (CeO2 -NPs). Abstract : Indoor aquatic mesocosms were designed to mimic pond ecosystems contaminated by a continuous point-source discharge of cerium oxide nanoparticles (CeO2 -NPs). Bare and citrate-coated CeO2 -NPs exhibited different chemical and colloidal behaviors in the aquatic mesocosms. Bare CeO2 -NPs were chemically stable but quickly homo-aggregated and settled out of the water column. Citrate-coated NPs both homo- and hetero-aggregated but only after the several days required to degrade the citrate coating. While they were more stable as a colloidal suspension, coated CeO2 -NPs dissolved faster due to surface complexation with citrate, which resulted in the release of dissolved Ce into the water column. The different distributions over time between water/sediment or dissolved/particulate forms of Ce controlled the availability of Ce to benthic grazers (mollusk Planorbarius corneus ) and planktonic filter feeders (copepod Eudiaptomus vulgaris ).